Modern sculpture and sculptors in east Africa - Todd, C. (International Library of African Music, 1961)
East Africa can make no claim to an artistic tradition of the past in any significant measure, and whatever of importance occurs in the field of the Fine Arts today does not rely upon, nor is it fortified by a sense of continuity in styles or forms that have their roots in past or surviving traditions. Therefore what can be seen of modern sculpture in East Africa is, in no sense, a Renaissance, but is rather a new birth, an upsurge of creative activity that belongs to this day and age.
Keywords: Sculptors; Ethnomusicology; Africa; Sculpture; East Africa; Uganda; African Music